Studies on Different Cultural Parameters on Vegetative Growth of Straw Mushroom (Volvariella volvacea) - Sharma, Shivani; Jarial, R. S.; Jarial, Kumud (International Journal of Bio-resource and Stress Management, 2020)
Volvariella volvacea is an edible straw mushroom of tropics and subtropics. The optimum temperature and moisture for the growth of this mushroom are 35 °C and 57-60%, respectively. Mushrooms grow on natural or semi synthetic compost and absorb nutrients for their survival. The maintenance and revival of pure culture mycelium with magnificent quality is the first critical stage towards the success of spawn preparation. To maintain any microorganism in artificial conditions, the former has to be cultured on a suitable nutrient medium. All microbes require a set of conditions under which they can grow and sporulate best and culture medium is the major factor influencing fungal cultivation. Five different culture media both in liquid and solid phase, five different pH levels and five temperature regimes were evaluated for the vegetative growth of four different strains of Volvariella volvacea i.e. DMR-484, DMR-463, DMR-819 and DMR-820. Among five liquid media studied, malt extract was found to be the best medium for the growth of all the strains of V. volvacea both in solid as well as in liquid phase. Out of five different pH levels evaluated for the growth of V. volvacea pH7.0 was observed to be the best pH for the growth of all the strains of the test fungus. Out of five different temperature regimes evaluated, 30 °C was observed to be the ideal temperature for the growth of V. volvacea.